2007
DOI: 10.1007/s00417-006-0525-x
|View full text |Cite
|
Sign up to set email alerts
|

Plasma endothelin-1 levels depress optic nerve head circulation detected during the glucose tolerance test

Abstract: ONH circulation increased after glucose intake in the normal glucose tolerance group and remained high even after the blood glucose level had returned to its baseline. The decrease in ONH circulation in the abnormal glucose tolerance group was attributed partly to the increased ET-1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…Kida et al examined optic nerve head (ONH) blood circulation during 75-gr OGTT. They concluded that ONH circulation decreased in the abnormal glucose tolerance group, attributed partly to the increased endothelin-1 [ 24 ]. In a similar study, authors investigated the microcirculation and progression of macular edema [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Kida et al examined optic nerve head (ONH) blood circulation during 75-gr OGTT. They concluded that ONH circulation decreased in the abnormal glucose tolerance group, attributed partly to the increased endothelin-1 [ 24 ]. In a similar study, authors investigated the microcirculation and progression of macular edema [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Before starting the measurement, a rest period of 5–10 mins should be scheduled in order to obtain stable systemic haemodynamic conditions, which should be verified by repeated measurements of systemic blood pressure and pulse rate. In addition, as a rise in blood glucose has been reported to increase ONH blood flow (Kida et al. 2001, 2007), clinical studies should be performed after a 2‐hour fasting period and a 6‐hour period of abstinence from coffee and alcohol.…”
Section: Clinical Protocolmentioning
confidence: 99%
“…2002), dynamic exercise (Okuno et al. 2006), glucose loading (Kida et al. 2007), various topical drugs (Tamaki et al.…”
Section: Reportingmentioning
confidence: 99%
“…Kida et al examined optic nerve head (ONH) blood circulation during 75-gr OGTT and concluded that ONH circulation decreased in the abnormal glucose tolerance group, attributed partly to the increased endothelin-1. 21 The significant positive correlation of GTT fasting and 1 hour values reflect the need for performing OCT along with glucose tolerance test as this helps in preventing early neurodegenerative changes occurring in RNFL. Thus uncontrolled blood sugar values brings about changes in the retinal microcirculation which causes thinning at the level of peripapillary optic nerve head or vice versa as evidence suggests that neurodegenerative changes occur prior to microvascular changes in diabetes.…”
Section: Comparison Of Blood Glucose Levels With Retinal Thinningmentioning
confidence: 99%